Contribution of Dr. Laza Popović to the development of Serbian and Yugoslav Sokol movement - Vukašinović Vladan; Mijatović Slađana; Šiljak Violeta; Veličković Saša; Strelić Dragan; Stevanović Miroslav (Vojnosanitetski Pregled, 2016)
nema